2022
DOI: 10.1161/jaha.121.022827
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Uroguanylin and D 1 Dopamine Receptors on Sodium Excretion in Hypertension

Abstract: Background Oral NaCl produces a greater natriuresis and diuresis than the intravenous infusion of the same amount of NaCl, indicating the existence of a gastro‐renal axis. As one of the major natriuretic hormones secreted by both the intestines and the kidney, we hypothesized that renal uroguanylin interacts with dopamine receptors to increase sodium excretion synergistically, an impaired interaction of which may be involved in the pathogenesis of hypertension. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
1
0
1
Order By: Relevance
“…In addition, dopamine regulates mitochondrial function, increases autophagy and reduces the generation of reactive oxygen species by the cAMP-PKA signaling pathway and the DR, which also plays a crucial function in the pathogenesis of hypertension [ 62 , 63 ]. Many studies have shown that animals/human hypertension/salt-sensitive hypertension is closely related to the abnormal regulation of dopamine receptors or dopamine production [ 60 , 64 , 65 ], and abnormal dopamine receptors may be related to increased G protein receptor kinase 4 activity [ 66 , 67 ]. Similarly, disruption of any dopamine receptor in mice causes high blood pressure [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dopamine regulates mitochondrial function, increases autophagy and reduces the generation of reactive oxygen species by the cAMP-PKA signaling pathway and the DR, which also plays a crucial function in the pathogenesis of hypertension [ 62 , 63 ]. Many studies have shown that animals/human hypertension/salt-sensitive hypertension is closely related to the abnormal regulation of dopamine receptors or dopamine production [ 60 , 64 , 65 ], and abnormal dopamine receptors may be related to increased G protein receptor kinase 4 activity [ 66 , 67 ]. Similarly, disruption of any dopamine receptor in mice causes high blood pressure [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Отримані дані щодо взаємодії між нирковим урогуаніліном та D1-рецепторами дозволяють припустити, що існує їх синергізм для збільшення екскреції натрію. Аберантна взаємодія між нирковим урогуаніліном та D1-подібними рецепторами може відігравати роль у порушеннях водо-та іонорегулювальної функції нирок і патогенезі артеріальної гіпертензії [27].…”
Section: огляд / Reviewunclassified